Comparing Approaches to Virtual Team Onboarding: the Influence of Synchrony and Cues on Impressions of Leaders During Encounter Phase Organizational Socialization - (:unkn) unknown (My University, 2023)
Whether fully virtual or a hybrid of virtual and face-to-face teams, more organizations use computer-mediated communication than ever before. Under the right circumstances, virtual team environments have been shown to increase employee satisfaction, retention, and productivity (Gallup, 2020). However, there is also consensus that virtual teams take longer to get work done and miscommunicate more frequently than face-to-face teams (Morrison-Smith & Ruiz, 2020). While there is no silver bullet to resolve these shortcomings, one potential area for intervention is during new employee onboarding. This study tests the hyperpersonal model and social presence theory’s application to virtual team onboarding by examining how message characteristics (synchronicity and degree of nonverbal cues) affect new employees’ sense of safety and impressions of their managers during their first moments on the job. The study finds no relationship between synchronicity and degree of nonverbal cues on employees’ sense of safety or impression of their managers. However, the study finds a marginally significant negative interaction effect between synchronicity and low nonverbal cues on impressions of virtual team leaders’ relational communication. Theoretical and practical implications for virtual team onboarding are discussed.
Keywords: hyperpersonal model; leadership communication; onboarding; relational communication; social presence; virtual teams